Piscivorous Bird Deterrent Device Based on a Direct Digital Synthesis of Acoustic Signals - Aboltins, Arturs; Pikulins, Dmitrijs; Grizans, Juris; Tjukovs, Sergejs (Elektronika ir Elektrotechnika, 2021)
This paper addresses the development of an acoustic deterrent device for the protection of fishponds and other objects against the unwanted presence of birds. The objective of the paper is not only providing of a deep analysis of available technologies for waveform synthesis and generation, but also building a theoretical base for the design and implementation of acoustic bird deterrent solutions. The paper addresses the synthesis of bird songs and calls using technologies for music, speech, and other types of acoustic signal processing. The second part of the paper is devoted to the unique algorithms and implementation details of the intelligent acoustic deterrence device prototype. The practical applicability of algorithms for bird call record conversion into synthesizer sequences has been analysed and possible issues are highlighted. The effectiveness and ease of practical implementation of the given method in the hardware are briefly discussed.